2013
DOI: 10.4155/bio.12.337
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Microsampling and Analysis of 4-µL Blood, Plasma and Serum Samples to Determine Human α-Synuclein Elimination Rate in Mice

Abstract: The small sample volumes and flexibility in choice of liquid matrices using the capillary microsampling technique enable repeated sampling in mouse studies, as well as multi-matrix analysis if needed. Liquid microsampling is well suited for micro- and nano-liter scale immunoassays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Typical CMS volumes for collecting blood microsamples are 8, 15 and 25 μl [3][4][5][6][7]. In our previous report, we used the smallest volume, 8 μl, for collecting blood samples for serial PK sampling in mouse PK studies [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical CMS volumes for collecting blood microsamples are 8, 15 and 25 μl [3][4][5][6][7]. In our previous report, we used the smallest volume, 8 μl, for collecting blood samples for serial PK sampling in mouse PK studies [9].…”
Section: Resultsmentioning
confidence: 99%
“…Two hurdles to collecting smaller volume samples are that it has to be performed in a way that is easy for the person collecting the small sample volume and it has to be processed in a way that makes the sample suitable for bioanalysis. Recently, Jonsson et al [3][4][5][6] described the utility of using capillary microsampling (CMS) for collecting blood samples from various laboratory animals including mice and rats; CMS was found to be a useful method for collecting small volumes (8-25 μl) of blood for various types of PK and TK studies. Recently, Dillen et al [7] reported using 15-μl CMS to obtain blood samples for discovery PK studies in the rat and dog.…”
mentioning
confidence: 99%
“…Recently, Joyce et al [8] described the use of blood CMS to collect serial samples from mice to allow for PK profiling of a dosed biotherapeutic compound; the dosed compound was a human IgG monoclonal antibody and the assay was based on ligand binding assay quantification. Very recently, Jonsson et al [9] described the utility of blood CMS to allow for PK sampling of blood from mice to assay for the 14-kDa protein, α-synuclein, via an immunoassay method.…”
mentioning
confidence: 99%
“…Vishwottam Kandikere (Advinus, India) started the session with a talk on plasma microsampling techniques for reducing the sampling volume in preclinical PK/toxicokinetic studies. He also elaborated on dialysis and capillary microsampling techniques [8][9][10] with relevant case studies. Echoing the microsampling theme, the second talk was delivered by Vijay Raina, who touched upon the DBS technique, highlighting the importance of sequential method development strategies in order to establish a sensitive and reproducible bioanalytical method.…”
Section: Discovery Bioanalysis Workhop: Day 3 (26 February 2014)mentioning
confidence: 99%